Optimization Of Electrical Submersible Pump Size To Increase Dr-01 Well Production Rate Of Field Puyuh - Agustina Prihantini; Nurkhozin Adhi Nugroho; Dliya Ruhana (LPPM Institut Teknologi Petroleum Balongan, 2025)
Abstract. The